Lipid peroxidation within different amaranth cultivars - Havugimana, Sylvestre; Kiseleva, Irina Sergeevna; Nsengumuremyi, Daniel (Brazilian Journal of Science, 2023)
In natural environments, plants are exposed to biotic and abiotic stresses during their whole life circle. Moreover, lipid peroxidation is a physiological indicator of the above stress responses, hence is often used as a biomarker to assess stress-induced cell damage or death. This study evaluated the lipid peroxidation of base and stress leaf discs for nine amaranth cultivars. The feasibility of optical density with λ = 532 and λ = 600 nm was investigated, and the malondialdehyde (MDA) concentration intensity was determined using the TBA method, especially the Thiobarbituric acid (TBA) extinction coefficient to detect its content. Furthermore, MDA values were ranging from 0.007 ± 0.001 mM/g-1 to 0.013 ± 0.002 mM/g-1 and from 0.016 ± 0.002 mM/g-1 to 0.035 ± 0.008 mM/g-1 for base and stress conditions respectively. This study represented high MDA content under water stress and low MDA content detection in leaves of A. caudatus L., A. hypochondriacus L., A. cruentus L., and A. hybridus L. cultivars. This indication defines the better antioxidant activity of these cultivars.